Feed improvement to support intensification of ruminant production systems in the Ethiopian highlands - Mohamed-Saleem, M.A.; Tedla, A. (Ethiopian Society of Animal Production, 1995)
This paper presents some strategies for feed improvement to support intensification of ruminant production in the Ethiopian highlands. It looks into feed availability, and outlines feed intensification strategies. Opportunities for feed improvement and management, feed improvement in intensified systems, and management of marginal lands are discussed.